It Takes a Village : Community-based Organizations and the Availability and Utilization of HIV/AIDS-related Services in Nigeria - Kakietek, Jakub; Geberselassie, Tesfayi; Manteuffel, Brigitte; Kayode, Ogungbemi; Krivelyova, Anya; Bausch, Sarah; Rodriguez-Garcia, Rosalia; Bonnel, Rene; N’Jie, N’Della; Fruh, Joseph; Gar, Sani (Taylor and Francis, 2013)
Community-based organizations (CBOs) have emerged as a vital part of the response to HIV/AIDs in Nigeria. The evaluation, on which this article is based, conducted in 28 communities in 6 states and the Federal capital Territory in Nigeria, assessed the effects of the CBO engagement on a set of outcomes related to HIV/AIDS knowledge, attitudes, beliefs, and practices, stigma, service availably and utilization and social capital. It consisted of three components: a household survey conducted in all 28 communities, qualitative data collected from CBO staff and key informants (KIs), and a funding allocation study (qualitative interviews and the funding allocation study were conducted in a subset of 14 communities). This article focuses on the association between CBO engagement and reported availability and utilization of HIV/AIDS-related services. It shows that CBO engagement has a potential to add value to the national response to HIV/AIDS by increasing the awareness, availability, and utilization of HIV/AIDS-related services, especially in the area of prevention, care and support. The CBOs in the evaluation communities focused on prevention activities as well as on providing support for people living with HIV/AIDS (PLWHA) and prevention and care and support were the highest expenditure categories reported by CBOs. Respondents in communities with a stronger CBO engagement were more likely to: (1) be aware of any HIV/AIDs-related services, (2) report that prevention and care services were available in their communities, and (3) have used any HIV/AIDS related services, prevention-related and care-related services than respondents in communities where CBO engagement was weaker. The association between service awareness and service use and CBO engagement was stronger in rural than in urban areas.